Practical Threat Detection Engineering A Hands-On Guide to Planning, Developing, and Validating Detection Capabilities - Roddie, Megan (Packt Publishing, Limited, 2023)
Go on a journey through the threat detection engineering lifecycle while enriching your skill set and protecting your organization Key Features Gain a comprehensive understanding of threat validation Leverage open source tools to test security detections Harness open source content to supplement detection and testing Book Description Threat validation is an indispensable component of every security detection program, ensuring a healthy detection pipeline. This comprehensive detection engineering guide will serve as an introduction for those who are new to detection validation, providing valuable guidelines to swiftly bring you up to speed. The book will show you how to apply the supplied frameworks to assess, test, and validate your detection program. It covers the entire life cycle of a detection, from creation to validation, with the help of real-world examples. Featuring hands-on tutorials, projects, and self-assessment questions, this guide will enable you to confidently validate the detections in your security program. By the end of this book, you'll have developed the skills necessary to test your security detection program and strengthen your organization's security measures. What you will learn Understand the detection engineering process Build a detection engineering test lab Learn how to maintain detections as code Understand how threat intelligence can be used to drive detection development Prove the effectiveness of detection capabilities to business leadership Learn how to limit attackers' ability to inflict damage by detecting any malicious activity early Who this book is for This book is for security analysts and engineers seeking to improve their organization's security posture by mastering the detection engineering lifecycle. To get started with this book, you'll need a basic understanding of cybersecurity concepts, along with some experience with detection and alert capabilities.